1994
DOI: 10.1164/ajrccm.149.3.8118641
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory responses during wakefulness in children with obstructive sleep apnea.

Abstract: The pathophysiology of the obstructive sleep apnea syndrome (OSAS) is not fully understood. In children, airway obstruction secondary to tonsilloadenoidal hypertrophy is the leading cause of OSAS. However, not all children with tonsilloadenoidal hypertrophy develop OSAS. Thus, other factors, including abnormalities in ventilatory control, may contribute to the etiology of OSAS. To test this, we performed polysomnography and hypercapnic and hypoxic ventilatory response testing in 20 children and adolescents wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 22 publications
2
30
3
Order By: Relevance
“…This was probably due to stimulation of the CNS, resulting in augmentation of upper airway neuromotor tone (7,34,35). Previously, we showed that children with OSAS had normal ventilatory responses to hypoxia and hypercapnia during both wakefulness (36) and sleep (35). Thus, their overall ventilatory drive appears to be normal.…”
Section: Neuromotor Control Of the Upper Airwaymentioning
confidence: 95%
“…This was probably due to stimulation of the CNS, resulting in augmentation of upper airway neuromotor tone (7,34,35). Previously, we showed that children with OSAS had normal ventilatory responses to hypoxia and hypercapnia during both wakefulness (36) and sleep (35). Thus, their overall ventilatory drive appears to be normal.…”
Section: Neuromotor Control Of the Upper Airwaymentioning
confidence: 95%
“…A number of studies have been performed in patients with OSAHS and their family members regarding hypercapnic and hypoxia ventilatory responses. The numbers are small and the results conflicting [14,49,50,51,52,53,54,55]. Whether respiratory control problems are implicated in the pathogenesis of OSAHS is open to debate.…”
Section: Intermediate Phenotypes Of Osahsmentioning
confidence: 99%
“…1,2 Children with SDB are more frequent users of health care services, 3 experience more frequent comorbid chronic illnesses, 4,5 and may develop significant clinical cardiovascular morbidity. 1,[6][7][8][9] They also display significant behavioral and cognitive comorbidities, 10 as well as reduced quality of life and mood alterations. 11 Animal models of SDB display long-term, partially irreversible neurocognitive consequences after intermittent hypoxia during sleep, particularly when such exposures occur early during development.…”
mentioning
confidence: 99%